Comparison Study Between SOI And Si MOSFET Based Inverter For EV Application Using MATLAB/Simulink - Firdaus, Firdaus; Razali, Muhammad Anas (Evolution in Electrical and Electronic Engineering, 2022)
An electrical device known as an inverter transforms electricity from a direct current (DC) source into an alternating current (AC) that can be utilized to power a device or appliance. The necessity for electric vehicles (EVs) to convert the electrical current required to charge them into the direct current needed to operate them creates a few significant difficulties such as high voltage-related temperature increases. The system’s temperature is likely to be increased since power is dissipated in the form of heat. The common material used for the electric vehicle inverter based on the previous study is Silicon Carbide. This paper focuses on the simulation model and calculation of losses by using two different materials which is Silicon on Insulator and Silicon. The switching and conduction losses were calculated using MATLAB/Simulink models of the devices. The results show that Silicon on Insulator MOSFET has lower conduction and switching losses and also for total power loss. It also shows that Silicon on Insulator MOSFET was superior compared to the Silicon MOSFET in terms of their overall characteristics.